Design of Smart Fuel Station and Management System Based on Arduino and Internet of Things - Budi Prijo Sembodo; Haris Atmajaya (Program Studi Teknik Elektro Universitas PGRI Adi Buana Surabaya, 2021)
Patrol that is distributed to the public must meet the requirement for the quality, quantity and continuity. Pertamina as one of the companies that is responsible for the distribution of patrol to the public through gas stations and must have competent management and services. However, problems arise in the community and even companies in controlling fuel consumption and queues for sales services at gas stations. One solution is to use a station that is connected to smartphone wirelessly and a cashless. Through the